Amendments and updates to F.C. Fraser’s key to Indian Lestes spp. (Odonata: Lestidae) to resolve confusion of L. patricia Fraser, 1924 and L. nigriceps Fraser, 1924, with notes on L. nodalis Selys 1891 and L. garoensis Lahiri, 1987 - Kosterin, Oleg E. (Zootaxa, 2019)
Last year I reported the rediscovery in Cambodia of Lestes nigriceps Fraser, 1924, described from Pusa, India (Fraser 1924a) but never reported since that time from India (Kosterin 2018). In my paper I presumed non-conspecificity of the male and females of the type series and made critical comments on Fraser’s appendage drawing (Fraser 1924a: plate IX: 6) and verbal descriptions (Fraser 1924a; 1933) of this species but did not consider his key for Lestes Leach, 1815 in the 1st volume of “Fauna of British India including Ceylon and Burma. Odonata” (Fraser 1933). Later I found a considerable corruption in this key, which could lead to misidentifications. (It is noteworthy to stress that Fraser explicitly provided keys for males only).